OPN5 Regulating Mechanism of Follicle Development Through the TSH-DIO2/DIO3 Pathway in Mountain Ducks Under Different Photoperiods - Liufu, Sui; Pan, Jianqiu; Sun, Junfeng; Shen, Xu; Jiang, Danli; Ouyang, Hongjia; Xu, Danning; Tian, Yunbo; Huang, Yunmao (Frontiers in Physiology, 2022)
Photoperiod is an important environmental factor that influence seasonal reproduction behavior in bird. Birds translates photoperiodic information into neuroendocrine signals through deep brain photoreceptors (DBPs). OPN5 has been considered as candidate DBPs involving in regulation of seasonal reproduction in birds. However, little is known about the effect of OPN5 in non-seasonal breeding birds. Thus, we pondered on whether OPN5 regulating follicular development through TSH-DIO2/DIO3 system responds to different photoperiods in non-seasonal laying ducks. As an ideal non-seasonal breeding bird, a total of 120 mountain ducks were randomly divided into three groups and treated respectively to a different photoperiod: group S (8L:18D), group C (17L:7D), and group L (24L:0D). The ducks were caged in a fully enclosed shelter with the same feeding conditions for each group, free water and limited feeding (150 g per duck each day). Samples were collected from each group at d 0, d 5, d 8, d 20, and d 35 (n=8). The ducks in 24 h photoperiod had the highest laying rate and the lowest feed-to-egg ratio, while the ducks in 8 h photoperiod had the lowest laying rate and the highest feed-to-egg ratio. Long-day photoperiod for 24 h significantly increased the ovarian index and GnRH, LH, E2, and P4 levels in serum; short-day photoperiod for 8 h increased PRL and testosterone levels in serum. Compared with 8 h photoperiod, long-day photoperiod significantly or highly significantly increased the mRNA level and protein expression of OPN5 in the hypothalamus of long-day photoperiod on d 35 (P<0.05). The gene or protein expression patterns of GnRH, TRH, TSHβ, DIO2, THRβ, VIP, and PRL were positively correlated with OPN5, whereas the gene expression patterns of GnIH and DIO3 were negatively correlated with OPN5. The results revealed that OPN5 mediated the effect of light on follicular development through the TSH-DIO2/DIO3 pathway, the expression of OPN5 increased with light duration and improved the efficiency of the HPG axis to promote follicular development in mountain ducks.